Hubungan antara Kepuasan Kerja dengan Kinerja pada Guru Sekolah Luar Biasa di Kota Samarinda - Putra, Hablullah Mustofa Pratama; Ashshiddiqi, Ali Mahmud (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study is aim to know the relationship between work performance and work satisfaction on special school’s teachers in Samarinda City. The hypothesis of this study is there is a positive correlations between work performance and work satisfaction on special school’s teachers. There are 60 teachers as subjects in this study, those are 16 men and 44 women. This study has used Koopmans’ work performance scale (2014) and Spector’s work safisfaction scale (1985). Result of Spearman correlation test shows that the correlation coefficient obtained by 0.369, with a significance value of 0.002 (p>0.05. There is a positive correlation between job satisfaction and work performance on special school’s teachers. Job satisfaction has an effect of 13.6% on performance seen from the coefficient of determination of (r²) = 0.136. The remaining 86.4% is the influence of other factors. Other findings indicate that by gender there was no difference in job satisfaction and performance between male and female respondents. Similarly, there is no difference in the two variables based on years of service. Other psychological factors for the performance of special school teachers still need to be investigated further.Keyword: work performance, work satisfaction, special school’s teachers